The Effect of Readiness Pattern for Patients Undergone General Anesthesia On State Anxiety in Srisangwornsukhothai Hospital Sukhothai Province - Puttaruk, Warangkana (Nursing Journal CMU, 2021)
State-anxiety is an emotional state that occurs at the time of stimulating events, that affect the thought process and the perception of the person changes. Especially surgery, in which most patients assessed as a life crisis and anxiety-inducing situation. Nurses Anesthetists’ role is patient preparation by providing information and knowledge related to surgery and anesthesia in reducing anxiety in helping patients decide to face different situations. This research is a quasi-experimental study. The aim was to compare the state anxiety levels in patients undergoing general anesthesia before and after receiving the readiness pattern with traditional education. The sample consisted of 64 patients who received surgery undergoing a general anesthesia was divided into a control group and a experimental group of 32 participants. 1) The control group was prepared before undergoing general anesthesia according normal anesthesia standards. 2) The experimental group was prepared using the readiness pattern of care for patients undergoing general anesthesia that the researcher created. Both groups were assessed for anxiety using the State-Trait Anxiety Inventory [STAI] form Y-1) before and after providing information on preoperative preparation. The results showed that the experimental group had mean scores for state anxiety before and after receiving the readiness pattern of care for patients undergoing general anesthesia of 43.12 ± 5.29 and 37.03 ± 4.91 respectively. The control group had mean scores for state anxiety before and after receiving normal anesthesia standards of 44.93 ± 4.46 and 48.15 ± 2.81 respectively. Prior to the implementation, the patients in both the control and experimental groups had no significant difference in scores of state anxiety scores, p = 0.810. After receiving the information, the patients in both groups had significantly lower state anxiety scores, p = 0.002 and p <0.001, respectively. When comparing state anxiety after implementation of both groups, it was found that a group of patients who received the readiness pattern for patients under general anesthesia, there was significantly less state anxiety than the non-receiving group, p = 0.048. Conclusion, the readiness pattern of care for patients undergoing general anesthesia it reduces state anxiety more than conventional preparation.